WAHBAH AZ-ZUHAILI AND MUHAMMAD SYAHRUR'S METHODS OF THINKING ABOUT MARRIAGE - Hidayat, Riyan Erwin; Suharto, S.; Bahrudin, Moh.; Zaki, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2022)
By the development of the times, of course the law will also experience various developments, as well as marriage law in Islam which follows the times according to human needs. The development of marriage law in Islam cannot be separated from the existence of Muslim scholars. Among these Muslim scholars are Wahbah az-Zuhaili and Muhammad Syahrur. Az-Zuhaili uses the Usul fiqh method in interpreting the laws regarding marriage, while Syahrur uses the hermeneutic method in interpreting the laws regarding marriage. The two of them certainly have different opinions, because the way of thinking and the method of interpretation used are different. Therefore, through this study, the two thoughts of these figures will be examined. The results showed that the two figures viewed marriage as a very solid contract. The difference of opinion between the two lies in the discussion of the dowry, where according to az-Zuhaili that the dowry is a gift from the husband to the wife, and the wife has the right to get it because of the contract or actual intercourse, while Syahrur said the dowry is an unconditional gift given by the husband to his wife. Likewise, there are differences of opinion in the provision of a living and in terms of divorce and polygamy.